Pathological examination for quality assurance in breast conserving therapy for breast cancer - Decker, Thomas (Radiology and oncology (Ljubljana), 1997)
Long-term survival in patients after breast conserving therapy (BCT) is similar to that after mastectomy. Nevertheless, there is a significant risk oflocal recurrence. Although local recurrence does not appear to affect the survival, there certainly is associated morbidity and attendant emotional trauma present. The margin status was shown to be a risk factor for local recurrence. Microscopic evaluation of the margins of lumpectomy specimens is the only way to define the extent of the tumour, especially of its intraductalcomponent, and the adequacy of resection. We intended to check the influence of a standardised protocol for pathological examination on the results of histological margin assessment. Moreover, we wanted to investigate the effects of margin status and size of the area of the DCIS-component on thechoice of treatment, Between February 1994 and February 1996, 582 women hadan unilateral breast excision at the Berlin-Buch Medical Centre. In 233 patients (71.8%) there were no clinical or mammographic contraindications for BCT and their carcinomas were treated by conservative surgery and irradiation.The aim of all tumour excisions was the complete removal of the tumour. As a result of our standardised margin investigation, in 28% of cases there was microscopic evidence of tumour tissue in the margins of 100 consecutive BCT specimens although the margins looked clear macroscopically. In two periods when histological investigations were not caried out on non suspicious-looking margins and the margin assessment was non-standardised, theevidence of tumour could be found in only 2% and 12% of the patients respectively. (Abstract truncated at 2000 characters.)
Keywords: Breast neoplasms; Enzymology; Radiotherapy; Surgery; Survival rate